Evaluation method for uniformity of lithium battery slurry
Through in-situ fluorescence labeling-spectral detection technology, BODIPY dye is used to label lithium battery slurry, which solves the problem of the inability to effectively detect slurry uniformity in existing technologies, realizes low-cost, high-sensitivity slurry uniformity evaluation, and improves the coating problem in the lithium battery production process.
Patent Information
- Application Number
- CN202510866706.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-09-26
AI Technical Summary
Existing technologies are unable to effectively detect the uniformity of lithium battery slurry, leading to problems such as screen clogging during coating and powder loss on the electrodes, which increases industrial manufacturing costs. In addition, existing detection methods are costly, time-consuming, and unable to provide real-time feedback.
In-situ fluorescence labeling-spectral detection technology is used to label lithium battery slurry with BODIPY dye. The slurry uniformity is evaluated through fluorescence slurry mixing, coating, ultrasonic extraction and spectral detection.
The sensitivity of slurry uniformity detection is improved, and the agglomeration of conductive agent and PVDF can be identified in real time, thus solving the clogging problem in the coating process and reducing the detection cost. It is suitable for a variety of lithium battery slurries.
Smart Images

Figure CN120703016A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of slurry uniformity evaluation, and in particular to a method for evaluating the uniformity of lithium battery slurry. Background Art
[0002] Currently, lithium-ion batteries are widely used in various applications due to their high energy density, high power density, and stable lifespan. In lithium-ion battery production, lithium battery slurry is a slurry composed of active materials, conductive agents, and binders uniformly mixed in a certain proportion to form a slurry with a certain viscosity. The uniformity of lithium battery slurry directly affects the quality of electrode sheets, battery cycle life, safety, and industrial process consistency.
[0003] Existing technologies typically rely on basic indicators such as viscosity and solids content, or on SEM / EDS methods to assess the uniformity of the slurry mixture and assess whether agglomeration of PVDF (polyvinylidene fluoride) and the conductive agent has occurred. However, these basic indicators cannot directly reflect the distribution of the conductive agent and binder, while SEM / EDS testing is costly, time-consuming, and lacks real-time feedback during the slurry mixing process. Furthermore, slurry non-uniformity can easily lead to problems such as screen clogging during coating and powder loss from the electrode, increasing industrial manufacturing costs. Therefore, a simple, low-cost method for evaluating slurry uniformity is urgently needed. Summary of the Invention
[0004] The object of the present invention is to provide a method for evaluating the uniformity of lithium battery slurry to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for evaluating the uniformity of lithium battery slurry, comprising the following steps: S1: Fluorescent agent dissolution: dissolve boron dipyrrolidone fluorescent dye (BODIPY) in N-methylpyrrolidone (NMP) solvent to prepare an NMP solution containing the fluorescent agent; S2: Fluorescent slurry: Mix the positive electrode active material, conductive agent, and binder in a certain proportion, then add the solvent containing BODIPY and knead them. Finally, add the conductive slurry and fully disperse it. Discharge the material after reaching the qualified viscosity, solid content, and fineness. S3: Coating and drying: Take multiple sample slurries, evenly coat them on the foil, label them respectively, and send the samples into the oven to fully bake them; S4: Scrape powder and weigh sample: Take out the baked electrode, scrape off the powder, and weigh 1-10g of powder. The weight of the powder weighed for each sample should be consistent. S5: Ultrasonic extraction: Take a container, add the powder sample, and add the same amount of dichloromethane for ultrasonic extraction; S6: Filtration and liquid collection: After ultrasonic extraction, the sample is filtered to obtain a clear and transparent solution sample; S7: Spectral detection and peak intensity analysis.
[0006] Preferably, S1 specifically comprises dissolving 0.5-1 g of BODIPY in 10-20 L of NMP solvent for later use.
[0007] Preferably, the slurrying method in S2 uses dry slurrying or wet slurrying.
[0008] Preferably, the baking temperature in S3 is 80-130° C., and the baking time is 0.5-5 hours.
[0009] Preferably, the ultrasonic extraction conditions in S5 are: ultrasonic time 10-90 min, frequency 20-80 kHz, power 150-600 W.
[0010] Preferably, the detection wavelength in S6 is 490-520 nm.
[0011] Preferably, the method is applicable to lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide or lithium cobalt oxide positive electrode slurry.
[0012] Preferably, in S7, solution samples are taken and placed in an ultraviolet absorption spectrometer or a fluorescence spectrometer for testing and data analysis.
[0013] The method is applicable to lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide or lithium cobalt oxide positive electrode slurry.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The lithium battery slurry uniformity evaluation method provided by the present invention uses an in-situ fluorescence labeling-spectral detection technology chain and utilizes the high molar extinction coefficient and narrow spectral half-width of BODIPY dye to increase the sensitivity of ultraviolet / fluorescence detection by more than 5 times. It can identify the agglomeration phenomenon of the conductive agent and PVDF during the slurry mixing process, thereby providing a basis for improving the slurry mixing process. With the help of the improvement of the slurry mixing process, the uniformity and consistency of the slurry can be improved, the quality control of the slurry intermediates can be carried out in real time, and the problem of screen clogging in the coating process can be solved. The only instruments used are ultraviolet spectrometers and fluorescence spectrometers. The equipment is relatively simple and the research cost is low.
[0015] This evaluation method does not limit the material system of the evaluation object. The mainstream lithium iron phosphate and ternary system positive electrode slurries on the market can be evaluated for their uniformity and consistency using the method provided by the present invention. Some oil-based negative electrode slurries can also be evaluated, and the usage scenarios are diverse. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is the synthetic reaction formula of BODIPY fluorescent dye; Figure 2 This is a diagram of BODIPY under natural light; Figure 3 This is the state diagram of BODIPY under ultraviolet light; Figure 4 is the UV / fluorescence spectrum of BODIPY; Figure 5 The UV spectra of the liquid with BODIPY added and the blank sample are compared; Figure 6 This is the UV spectrum comparison chart of the test sample; Figure 7 This is a comparison chart of the ultraviolet spectra of the non-uniform slurry sample in Example 1; Figure 8 This is the SEM / EDS electron microscope image of the sample in Example 1; Figure 9 This is a comparison chart of the UV spectrum of the uniform slurry sample in Example 2; Figure 10 This is the SEM / EDS electron microscope image of the sample in Example 2. DETAILED DESCRIPTION
[0017] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0018] Dipyrromethene Boron Difluoride (BODIPY) is a type of fluorescent dye that has attracted widespread attention and has the following excellent photophysical properties: ① High fluorescence quantum yield. Some fluorescent dyes can even achieve a fluorescence quantum yield of 1.0 in water, such as Figure 1 As shown in the figure; ② The fluorescence signal is insensitive to the polarity and pH of the solvent; ③ It has relatively good photothermal stability; ④ The fluorescence spectrum has a narrow half-peak width, which has good sensitivity when used as a fluorescent marker; ⑤ High molar extinction coefficient, usually greater than 80,000 L·mol -1 cm -1 ⑥ The structure is easy to modify, and the emission wavelength can be tuned to the near-infrared region. Given these advantages, BODIPY dyes are also widely used as phosphors in fluorescent sensors, biomarkers, photodynamic therapy, and organic light-emitting diodes.
[0019] BODIPY dyes can be purchased directly or prepared in the laboratory.
[0020] The preparation method in the laboratory is as follows: Please refer to the reaction formula Figure 1 To a 100 ml eggplant-shaped flask, add 25 ml of freshly distilled CH2Cl2 and flow N2 through the flask for 10 minutes. Protect from light with tin foil and place under a N2 balloon. Stir at room temperature. Add benzaldehyde (2 mmol, 0.21 ml) and 2.4-dimethylpyrrole (4 mmol, 0.41 ml) using a disposable syringe. Add one drop of TFA to 2 ml of freshly distilled CH2Cl2, then syringe-dose 1 ml into the reaction flask. Allow to react for a period of time, until the color changes from orange to wine red. After 5 hours, add DDQ (2.2 mmol, 499.4 mg), which deepens the color. After 2 hours, add 3 ml of TEA and 3 ml of BF3Et2O to the flask. TLC confirms the completion of the reaction.
[0021] After fully reacting for 4 hours, the organic phase was washed with distilled water, extracted with CH2Cl2, and dried over anhydrous sodium sulfate. The organic phase was purified by column chromatography using 10% EA / PE as the eluent to obtain an orange-yellow solid (188 mg, yield 27%). 1H NMR (400 MHz, CDC l3 ): δ=7.41–7.37 (m, 3H), 7.26-7.29 (m, 2H), 5.98 (s, 2H), 2.56 (s, 6H), 1.37 ppm (s, 6H).
[0022] Finished products such as Figure 2-3 shown.
[0023] like Figure 4 As shown, the UV absorption spectrometer peak of BODIPY in dichloromethane solvent is 501 nm, and the fluorescence spectrometer peak is 514 nm.
[0024] Accordingly, the present invention provides a technical solution: a method for evaluating the uniformity of lithium battery slurry, comprising the following steps: S1: Dissolving the fluorescent agent: Dissolve 0.5-1 g of BODIPY in 10-20 L of NMP solvent for later use.
[0025] S2: Fluorescent slurry: Since conventional negative electrodes are all water-based slurries, this technology is used in positive electrode slurry. Dry or wet slurrying is used. First, the positive electrode active material (lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide), conductive agent, and binder are mixed in a certain proportion, and then a solvent containing BODIPY is added for kneading. Finally, the conductive slurry is added and fully dispersed to achieve the qualified viscosity, solid content, and fineness before discharging.
[0026] S3: Coating and drying: Then take 10 to 20 sample slurries and evenly coat them on the foil using a small coating machine in the laboratory, which are recorded as samples 1 to 20 respectively. Send the samples to the oven and bake them at 80 to 130 ° C for 0.5 to 5 hours to fully bake them.
[0027] S4: Scrape powder and weigh sample: Take out the baked electrode, scrape off the powder, and weigh 1~10g of powder. The weight of the powder weighed for each sample is consistent with an error of 0.1%.
[0028] S5: Ultrasonic extraction: Take 10 to 20 50 or 100 ml small beakers and add powder samples one by one. Add the same mass of dichloromethane for ultrasonic extraction. The ultrasonic extraction time is 10-90 minutes, the ultrasonic extraction frequency is 20-80kHz, and the ultrasonic extraction power is 150-600W.
[0029] S6: Filtration and liquid collection: After ultrasonic extraction, the sample is filtered to obtain clear and transparent solution samples 1-20.
[0030] S7: Spectral detection and peak intensity analysis: Take solution samples and place them into UV absorption spectrometer or fluorescence spectrometer for testing and data analysis.
[0031] Repeat the above steps S3-S7 with the electrode without any BODIPY added. The obtained liquid is recorded as a blank sample. The UV spectrometer test reveals that Figure 5 As shown in the figure, the blank sample does not show any peak between 300 and 700 nm, while the addition of BODIPY shows an obvious peak at around 501 nm. This shows that BODIPY, as a fluorescent marker, can be well applied in the field of lithium battery slurry detection.
[0032] Then, the solution samples prepared in the above steps are tested by UV spectrum. Assuming that the test sample quantity is 10, Figure 6 As shown, if the peak intensities of the ten samples show no significant difference, this indicates that the PVDF is fully dissolved under the slurrying process, with no obvious micelles present, and the slurry is uniform and consistent. Due to strict control of powder scraping quality and solvent usage, theoretically, the slurry is uniformly mixed and the BODIPY concentration extracted by ultrasonic extraction is consistent, with no significant deviations. Example 1
[0033] Dissolve 0.5-1 g of BODIPY in 10-20 L of NMP solvent for later use.
[0034] This slurry was prepared using a dry process. First, lithium iron phosphate, conductive agent, and binder were mixed at a ratio of 96.3:1.0:2. Then, a solvent containing BODIPY was added and kneaded. Finally, conductive paste (solids content 0.7%) was added and fully dispersed until the desired viscosity of 6000-12000 mPa.s and solids content of 60-64% were achieved before discharging. The following steps were then performed: Ten slurry samples were taken from different positions of the mixing pot and evenly coated on the foil using a small coating machine in the laboratory, and were recorded as samples 1 to 10. The samples were sent to the oven and baked at 120℃ for 2 hours to fully bake them.
[0035] After baking, the electrode was taken out and the powder was scraped off. 10g of powder was weighed. The weight of the powder weighed for each sample was consistent with an error of 0.01g. Take 10 50ml small beakers and add the powder sample one by one. Add 25g of dichloromethane to each beaker for ultrasonic extraction. The ultrasonic extraction time is 30min, the ultrasonic extraction frequency is 50kHz, and the ultrasonic extraction power is 300W. After ultrasonic extraction, the samples were filtered to obtain clear and transparent solution samples 1 to 10; Take solution samples respectively and put them into UV absorption spectrometer or fluorescence spectrometer for testing and data analysis.
[0036] During the test, it was found that there were significant differences in peak intensities between two samples, such as Figure 7 As shown, it means that the slurry produced by this slurry mixing process has obvious defects. The powder and solvent may not be fully mixed, and agglomerates may be formed or the conductive agent may be agglomerated. There is a certain risk in the slurry.
[0037] The lithium iron phosphate cathode sheet made of non-uniform slurry was sent out for inspection using SEM / EDS electron microscope, such as Figure 8 The elemental analysis is shown in the following table.
[0038]
[0039] Elemental analysis shows that the main element is C, which is actually O. This shows that the conductive agent and PVDF agglomerated during the slurry mixing process, and the conductive agent and binder were not completely dispersed.
[0040] Targeted improvements need to be made to the slurry mixing process or materials to achieve the desired uniform mixing. Example 2
[0041] The same material ratio is used for wet slurrying, that is, PVDF is first dissolved in NMP solvent containing BODIPY to form PVDF glue, which is fully dispersed until the glue is clear and transparent, and then set aside.
[0042] In the mixing pot, PVDF glue, conductive agent, and conductive paste are added in sequence to make conductive glue. Finally, lithium iron phosphate is added and fully dispersed to reach the qualified viscosity of 6000~12000mPa.s and solid content of 60~64%. Then the following steps are carried out: Ten sample slurries were taken from different positions of the mixing pot and evenly coated on the foil using a small coating machine in the laboratory. They were recorded as samples 1 to 10.
[0043] The samples were placed in an oven and baked at 120°C for 2 hours to ensure thorough baking.
[0044] After baking, the electrode was taken out, the powder was scraped off, and 10g of powder was weighed. The weight of the powder weighed for each sample was consistent with an error of 0.01g.
[0045] Take 10 50ml small beakers and add powder samples one by one. Add 25g of dichloromethane to each beaker for ultrasonic extraction. The ultrasonic extraction time is 30min, the ultrasonic extraction frequency is 50kHz, and the ultrasonic extraction power is 300W.
[0046] After ultrasonic extraction, the samples were filtered to obtain clear and transparent solution samples 1-10.
[0047] Take solution samples respectively and put them into UV absorption spectrometer or fluorescence spectrometer for testing and data analysis.
[0048] Then, ultraviolet spectrum test is performed on the solution samples prepared in the above steps in sequence.
[0049] like Figure 9 As shown in the figure, there is no significant difference in the peak intensities of the 10 samples tested, which means that under this slurrying process, PVDF is fully dissolved, no obvious micelles appear, and the slurry has good uniformity and consistency.
[0050] Take the corresponding positive electrode sheet and send it out for inspection using SEM / EDS electron microscope for testing, such as Figure 10 As shown, the results show that the obvious micelle phenomenon in Example 1 does not occur, indicating that compared with the wet slurrying method, the wet slurrying method can effectively improve the PVDF micelle phenomenon.
[0051] At the same time, it is also proved that the present invention provides a method for evaluating the uniformity of lithium battery slurry as an effective detection method for the slurry mixing process, which can effectively judge the uniformity of the slurry mixing slurry in a timely manner when the detection equipment is in short supply. It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be embodied in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims, not the foregoing description, and all variations that come within the meaning and range of equivalents of the claims are intended to be embraced therein. Any reference sign in a claim should not be construed as limiting the claim to which it relates.
[0052] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for evaluating the uniformity of lithium battery slurry, characterized by: The steps include: S1: Fluorescent agent dissolution: dissolve boron dipyrrolidone fluorescent dye (BODIPY) in N-methylpyrrolidone (NMP) solvent to prepare an NMP solution containing the fluorescent agent; S2: Fluorescent slurry: Mix the positive electrode active material, conductive agent, and binder in a certain proportion, then add the solvent containing BODIPY and knead them. Finally, add the conductive slurry and fully disperse it. Discharge the material after reaching the qualified viscosity, solid content, and fineness. S3: Coating and drying: Take multiple sample slurries, evenly coat them on the foil, label them respectively, and send the samples into the oven to fully bake them; S4: Scrape powder and weigh sample: Take out the baked electrode, scrape off the powder, and weigh 1-10g of powder. The weight of the powder weighed for each sample should be consistent. S5: Ultrasonic extraction: Take a container, add the powder sample, and add the same amount of dichloromethane for ultrasonic extraction; S6: Filtration and liquid collection: After ultrasonic extraction, the sample is filtered to obtain a clear and transparent solution sample; S7: Spectral detection and peak intensity analysis.
2. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: S1 specifically comprises dissolving 0.5-1 g of BODIPY in 10-20 L of NMP solvent for later use.
3. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: The slurrying method in S2 uses dry slurrying or wet slurrying.
4. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: The baking temperature in S3 is 80-130° C., and the baking time is 0.5-5 hours.
5. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: The ultrasonic extraction conditions in S5 are: ultrasonic time 10-90 min, frequency 20-80 kHz, power 150-600 W.
6. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: The detection wavelength in S6 is 490-520 nm.
7. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: The method is applicable to lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide or lithium cobalt oxide positive electrode slurry.
8. The method for evaluating the uniformity of lithium battery slurry according to claim 1, wherein: In S7, solution samples are taken and placed in an ultraviolet absorption spectrometer or a fluorescence spectrometer for testing and data analysis.